The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/ejoc.200800943
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Hydrogenation of α‐Keto Phosphonates with Chiral Palladium Catalysts

Abstract: Under atmospheric hydrogen pressure, a catalytic amount of palladium(II) trifluoroacetate and (R)-MeO-BIPHEP in 2,2,2-trifluoroethanol promoted the asymmetric hydrogenation of diisopropyl α-keto phosphonates 1 to afford the corresponding α-hydroxy phosphonates 2 in excellent yields and with a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 72 publications
0
27
0
Order By: Relevance
“…The asymmetric hydrogenations of a-phthalimide ketones and a-keto phosphonates with palladium catalyst systems were reported by us [8] and Goulioukina, [9] respectively. In comparison, there are more reports on Pd-catalyzed asymmetric hydrogenations of activated imines.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The asymmetric hydrogenations of a-phthalimide ketones and a-keto phosphonates with palladium catalyst systems were reported by us [8] and Goulioukina, [9] respectively. In comparison, there are more reports on Pd-catalyzed asymmetric hydrogenations of activated imines.…”
mentioning
confidence: 88%
“…MeOH and CH 2 Cl 2 led to very low reactivity (entries 13 and 14); TFE was found to be the optimal solvent, which is in accordance with the Pd-catalyzed hydrogenation of ketones and activated imines in the literature. [8][9][10][11][12][13][14][15][16] Subsequently, some commercially available bisphosphine ligands were examined under the above conditions. The results showed that axial chiral bidentate bisphosphine ligands L1-L4 and L6-L8 (Table 2, entries 1-4 and 6-8) gave full conversions with 58-75% ee.…”
mentioning
confidence: 99%
“…The absolute configuration of the C*ÀP stereocenter was established as (R) by anomalous dispersion effects in diffraction measurements on a single crystal (Figure 4). [41] Speaking of regularities observed, we can sum up that the homogeneous palladium-catalyzed hydrogenation of a-oxo phosphonates [35] and E-isomers of the corresponding oximes [14] and tosylimines [6] using (R)-ligands of the binaphthyl and biphenyl types provides (S)-enantiomers of the products, but the hydrogenation of Z-oximes and Z-phenylhydrazones affords (R)-enantiomers. A tentative mechanism for homogeneous Pd(II)-catalyzed asymmetric hydrogenation can be outlined on the basis of previous investigations of Zhou et al, [12c] which include isotope-labeling tests, [26,28,42] NMR experiments, and DFT calculations [28] and taking into account general mechanistic aspects.…”
mentioning
confidence: 95%
“…[26,28,35,37] Among atropoisomeric C 2 -symmetric bidentate ligands of the triarylphosphine type only (S)-2,2'-bis(diphenylphospino)-5,5',6,6',7,7',8,8'-octahydro-1,1'-binaphthyl [(S)-H 8 -BINAP] (entry 4) showed an unsatisfactory result. It is worth mentioning that a characteristic feature of (S)-H 8 -BINAP is an appreciably increased dihedral angle between the planes of the aromatic fragments.…”
mentioning
confidence: 96%
“…Recently, Goulioukina reported the asymmetric hydrogenation of a-ketophosphonates 115 catalyzed by Pd(OCOCF 3 ) 2 /(R)-MeO-BiPhep in TFE under atmospheric hydrogen pressure with up to 55% ee (Scheme 39) [129]. …”
Section: Adventure In Asymmetric Hydrogenationmentioning
confidence: 99%